Nilotinib versus imatinib for the treatment of patients with newly diagnosed chronic phase, Philadelphia chromosome-positive, chronic myeloid leukaemia: 24-month minimum follow-up of the phase 3 randomised ENESTnd trial - Kantarjian, Hagop M; Hochhaus, Andreas; Saglio, Giuseppe; Souza, Carmino De; Flinn, Ian W; Stenke, Leif; Goh, Yeow-Tee; Rosti, Gianantonio; Nakamae, Hirohisa; Gallagher, Neil J; Hoenekopp, Albert; Blakesley, Rick E; et al. (The lancet oncology, 2011)
Nilotinib has shown greater efficacy than imatinib in patients with newly diagnosed Philadelphia chromosome-positive chronic myeloid leukaemia (CML) in chronic phase after a minimum follow-up of 12 months. We present data from the Evaluating Nilotinib Efficacy and Safety in clinical Trials–newly diagnosed patients (ENESTnd) study after a minimum follow-up of 24 months. ENESTnd was a phase 3, multicentre, open-label, randomised study. Adult patients were eligible if they had been diagnosed with chronic phase, Philadelphia chromosome-positive CML within the previous 6 months. Patients were randomly assigned (1:1:1) to receive nilotinib 300 mg twice a day, nilotinib 400 mg twice a day, or imatinib 400 mg once a day, all administered orally, by use of a computer-generated randomisation schedule, using permuted blocks, and stratified according to Sokal score. Efficacy results are reported for the intention-to-treat population. The primary endpoint was major molecular response at 12 months, defined as BCR–ABL transcript levels on the International Scale (BCR–ABL IS) of 0·1% or less by real-time quantitative PCR in peripheral blood. This study is registered with ClinicalTrials.gov, number NCT00471497. 282 patients were randomly assigned to receive nilotinib 300 mg twice daily, 281 to receive nilotinib 400 mg twice daily, and 283 to receive imatinib. By 24 months, significantly more patients had a major molecular response with nilotinib than with imatinib (201 [71%] with nilotinib 300 mg twice daily, 187 [67%] with nilotinib 400 mg twice daily, and 124 [44%] with imatinib; p<0·0001 for both comparisons). Significantly more patients in the nilotinib groups achieved a complete molecular response (defined as a reduction of BCR–ABL IS levels to ≤0·0032%) at any time than did those in the imatinib group (74 [26%] with nilotinib 300 mg twice daily, 59 [21%] with nilotinib 400 mg twice daily, and 29 [10%] with imatinib; p<0·0001 for nilotinib 300 mg twice daily vs imatinib, p=0·0004 for nilotinib 400 mg twice daily vs imatinib). There were fewer progressions to accelerated or blast phase on treatment, including clonal evolution, in the nilotinib groups than in the imatinib group (two with nilotinib 300 mg twice daily, five with nilotinib 400 mg twice daily, and 17 with imatinib; p=0·0003 for nilotinib 300 mg twice daily vs imatinib, p=0·0089 for nilotinib 400 mg twice daily vs imatinib). At 24 months, survival was comparable in all treatment groups, but fewer CML-related deaths had occurred in both the nilotinib groups than in the imatinib group (five with nilotinib 300 mg twice daily, three with nilotinib 400 mg twice daily, and ten with imatinib). Overall, the only grade 3 or 4 non-haematological adverse events that occurred in at least 2·5% of patients were headache (eight [3%] with nilotinib 300 mg twice daily, four [1%] with nilotinib 400 mg twice daily, and two [<1%] with imatinib) and rash (two [<1%], seven [3%], and five [2%], respectively). Grade 3 or 4 neutropenia was more common with imatinib than with either dose of nilotinib (33 [12%] with nilotinib 300 mg twice daily, 30 [11%] with nilotinib 400 mg twice daily, and 59 [21%] with imatinib). Serious adverse events were reported in eight additional patients in the second year of the study (four with nilotinib 300 mg twice daily, three with nilotinib 400 mg twice daily, and one with imatinib). Nilotinib continues to show better efficacy than imatinib for the treatment of patients with newly diagnosed CML in chronic phase. These results support nilotinib as a first-line treatment option for patients with newly diagnosed disease. Novartis.